Penularan Potyvirus Penyebab Penyakit Mosaik pada Tanaman Nilam melalui Vektor Aphis gossypii - Rita Noveriza; Gede Suastika; Sri Hendrastuti Hidayat; Utomo Kartosuwondo (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2012)
Patchouli (Pogostemon cablin) is an economically important plant due to its capability to produce essential oil, i.e. patchouli oil. Pest and diseases may contribute to low production of patchouli oil in Indonesia. Aphids are commonly found associated with patchouli plants showing mosaic symptoms, indicated possible relationship between aphids and mosaic virus. Early diagnosis showed that mosaic disease on patchouli is caused by Potyvirus infection. A study was conducted to identify those aphid species and to examine relationship between the aphid species and mosaic virus. Two aphid species commonly found in patchouli plants in Indonesia are Aphis gossypii and Brachycaudus sp. Further study on the ability of A. gossypii to transmit Potyvirus revealed the possible non-persistent relationship, with 25 min optimum pre-acquisition starvation, 15 min acquisition period and 4 hours optimum inoculation feeding period, respectively.Key words: Aphis gossypii, Brachycaudus, nilam, Pogostemon cablin, Potyvirus